Disparity in the Doctrine of Promissory Estoppel between Indonesia, the Philippines and the United Kingdom - Dolot Alhasni Bakung; Thanh Nga Pham; Mohamad Hidayat Muhtar (Journal of Law and Legal Reform, 2024)
There is a legal vacuum that regulates the settlement and legal consequences of pre-contractual promises between parties in Indonesia. This research aims to examine the legal application of the Promissory Estoppel Doctrine in filling legal gaps while comparing it with a number of Common Law countries, including England, which implemented this doctrine earlier. This research uses normative legal research using a comparative approach, case approach and conceptual approach. The sources of legal materials in this research consist of primary, secondary and tertiary legal materials. The application of the Promissory Estoppel doctrine to the Indonesian legal system can be done because there are similarities between the legal system in common law (England, the Philippines) and the legal system in Indonesia, so that courts in Indonesia can use this doctrine to fill legal gaps. Pre-contracts have been regulated in such a way both through legislation and the application of relevant legal doctrines in a number of developed countries. with the doctrine of promissory estoppel, an agreement that has not fulfilled certain conditions or objects, in this case a pre-agreement, can protect a party who has placed a trust in another party in the process of carrying out negotiations which causes him to carry out certain legal actions (rechtshandeling) and causes the birth of reliance. loss. Promissory estoppel is an important concept in English law however, the legal requirements for promissory estoppel may differ from country to country.